A DFT+U study of A-site and B-site substitution in BaFeO3−δ1. Issue 36 (28th September 2015) - Baiyee, Zarah Medina; Chen, Chi; Ciucci, Francesco
<x xml:space="preserve">Abstract</x> A physical insight on the A- and B-site substitution of BaFeO3 with focus on oxygen deficiency and electronic behaviour.